Study of procedures used to measure the energy spent running on the belt using mobile - Jassim, Mohammed; Jawad , Zaydoon (Journal of Physical Education, 2012)
The study included five sections:Section I: Introduction and included the importance of research and refers to the importance of the expense of energy expended during work on the mobile belt, which uses the majority of athletes or no athletes. The second section included topics theoretical studies, including (job, and the belt moving, and energy), while consisted Part III on the research methodology as was used descriptive method to nature properties of the problem while the sample was female College Education for Girls in the fourth row the number of six students conducted them tests running on the mobile belt. Part IV The presentation and analysis of results and discussion and based on the data obtained by the researcher was able to develop a set of conclusions and recommendations in Chapter Five .